Understanding PrEP decision making among pregnant women in Lilongwe, Malawi: A mixed‐methods study. Issue 9 (8th September 2022) - Hill, Lauren M.; Golin, Carol E.; Saidi, Friday; Phanga, Twambilile; Tseka, Jennifer; Young, Alinda; Pearce, Lisa D.; Maman, Suzanne; Chi, Benjamin H.; Mutale, Wilbroad
Abstract: Introduction: Pre‐exposure prophylaxis (PrEP) is a promising tool for HIV prevention during pregnancy. With increasing rollout in antenatal settings, counselling strategies to help pregnant women make appropriate decisions about PrEP use are needed. Understanding women's motivations and concerns for PrEP use—and how these inform their decision making and feelings about the decision to start PrEP—are critical to inform these strategies. Methods: We conducted a convergent mixed‐methods study from June 2020 to June 2021 in the context of a PrEP adherence support trial among HIV‐negative pregnant women in Lilongwe, Malawi. Two hundred women completed a survey reporting their motivations and concerns about PrEP use, and their feelings about the decision to start PrEP (Decisional Regret Scale). Thirty women completed in‐depth interviews to better understand the decision‐making process, including motivations and concerns weighed in women's decision to use PrEP. Analyses comprised descriptive and bivariate statistics, thematic qualitative analysis, and integration of quantitative and qualitative results. Results: Women initiating PrEP during pregnancy were highly motivated to obtain HIV protection for themselves and their unborn child, often due to perceived HIV risk connoted by a recent sexually transmitted infection and/or concerns about partner non‐monogamy. These motivations prevailed despite some concerns about safety and side effects, anticipated stigmatization, and concerns about adherence burden and pill attributes. Many women had informed their partner of their decision to use PrEP yet few felt their decision was contingent upon partner approval. Most women felt positively about the decision to start PrEP (mean decisional regret = 1.2 out of 5), but those with a greater number of concerns reported greater decisional regret (B = 0.036; p = 0.005). Furthermore, women who were specifically concerned about partner disclosure, who disliked pills or who had no perceived HIV risk reported greater decisional regret. Conclusions: Pregnant women were strongly motivated by the promise of HIV protection offered by PrEP and accepted it despite diverse concerns. A shared decision‐making approach that centres pregnant women and offers partner involvement may help identify and address initial concerns about PrEP use and support prevention‐effective use of PrEP during this important period.